The role of curriculum advisors in supporting teachers to curriculum policies in the Capricorn District of Limpopo Province - Seshoka, Matome Winter (My University, 2016)
The purpose of this study was to explore how district office Curriculum Advisors (CAs) support teachers to implement curriculum policies requirements in the Capricorn District of the Limpopo Province. This exploratory case study addressed this knowledge gap by exploring the lived experiences of ten CAs in one district. Data was constructed through semi-structured interviews, observations and document analysis. This study revealed various forms of support that CAs offer to teachers, challenges they face and suggestions/strategies they use to deal with them. The kind of support CAs offer to teachers can be categorized into five themes: training, monitoring, moderation, setting tasks and enrichment programmes. Generally, the study also revealed that there are significant challenges to CAs‟ ability to effectively practise curriculum support. These include: overload due to shortage of CAs, lack of resources, political interference and challenges from teachers. Furthermore, CAs used teamwork and sacrifice as their way of dealing with these challenges. They also provided suggestions which the government may employ to eradicate these challenges. In conclusion, the study provides six recommendations related to policy-makers and government, and implications for future research. KEY CONCEPTS Curriculum Advisors, curriculum support, teachers.
Thesis (M.Ed.(Curriculum studies)) -- University of Limpopo, 2016
Keywords: Curriculum advisors; Teachers; Curriculum policy implementation; Capricorn District; Limpopo Province; School support teams; Curriculum evaluation